UJI AKTIVITAS ANTIBAKTERI EKSTRAK DAUN SERAI WANGI (CYMBOPOGON NARDUS) TERHADAP BAKTERI PROPIONIBACTERIUM ACNES - Brigad Mahardika Winato; Erfan Sanjaya; Lisdawaty Siregar; Solinia Kifami Yohana Maria Vianne Fau; dr. Maya Sari Mutia (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2019)
Acne is a disease of the skin that often occurs during adolescence until adulthood. Acne is characterized by the appearance of several signs, namely blackheads, pustules, papules, cysts and nodes in the neck, face, upper arms, back and chest area. Acne is also a skin disease that affects more than 85% of adolescents around the world. Although not life-threatening, acne can affect a person's quality of life by giving a psychological effect that is bad for the sufferer in the form of a person's way of judging, responding to and looking at his condition and situation. The purpose of this study was to determine the inhibitory power of citronella extract (Cymbopogon nardus) on the growth of Propionibacterium acnes bacteria. The study was conducted with experimental methods with the posttest design only group design controls conducted at the Microbiology Lab at the Faculty of Medicine, University of Prima Indonesia and the Pharmacy and Toxicology Lab at the Faculty of Pharmacy, University of North Sumatra. The results showed that lemongrass leaf extract had a inhibitory effect on the growth of Propionibacterium acnes bacteria with various concentrations of 20, 40, 60, 80 and 100%. The higher the concentration of fragrant lemongrass extract, the better the inhibition power.